TO THE FIGHT QUESTION AGAINST ILLICIT TRAFFICKING IN THE NARCOTIC MEANS AND PSYCHOTROPIC SUBSTANCES IN THE REPUBLIC OF KAZAKHSTAN - Abdykarimova Алма Сагындыковна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
Article is devoted to questions of a sovershenstvaniye of criminal rules of law of trafficking in narcotics, psychotropic substances, precursors and counteraction to their illicit trafficking, in particular, to relevance of standards of the Criminal code of the Republic of Kazakhstan (new edition).